ECOLOGICAL EDUCATION IN THE PROPHET’S HADITHS: A THEMATIC STUDY ON HADITHS RELATED TO THE ENVIRONMENT - Edy Kurniawan Awan; Romlah Abubakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
Environmental awareness among humans regarding the importance of preserving nature—bestowed by Allah as a means to sustain life—is gradually declining. Irresponsible human actions frequently lead to environmental damage and ecological imbalance. If left unaddressed, such behavior poses serious threats to the continuity of life. This study aims to explore the Prophet Muhammad’s hadiths that emphasize the importance of environmental preservation. Employing a qualitative method with a literature review approach, this research analyzes relevant hadiths and scholarly interpretations. The findings reveal that the Prophet’s teachings on ecological preservation are comprehensive and highly relevant to contemporary environmental challenges. Most environmental degradation is a direct result of human actions, and the prophetic hadiths offer foundational solutions—framing what can be understood as an early model of ecological education in Islam. Keywords : Ecological education, hadith, environment